2018
DOI: 10.1002/ana.25376
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance T1w/T2w ratio: A parsimonious marker for Parkinson disease

Abstract: Objective: Newer MRI techniques have shown promise in capturing early Parkinson’s disease (PD)-related changes in the substantia nigra pars compacta (SNc), the key pathological loci. Their translational value, however, is hindered by technical complexity and inconsistent results. Methods: A novel yet simple MRI contrast, the T1w/T2w ratio, was used to study 76 PD patients and 70 controls. The T1w/T2w ratio maps were analyzed using both voxel-based and region-of-interest approaches in normalized space. The se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 39 publications
3
22
0
Order By: Relevance
“…Recent transcriptomic studies have further observed correlations of the T1-w/T2-w intensity in the cortex with expression of genes associated with cortical microcircuit specialization and myelin (Burt et al, 2018;Ritchie, Pantazatos, & French, 2018). In contrast, recently a study with Parkinson disease patients showed a higher T1-w/T2-w ratio in the substantia nigra pars compacta compared to controls (Du, Lewis, Sica, Kong, & Huang, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Recent transcriptomic studies have further observed correlations of the T1-w/T2-w intensity in the cortex with expression of genes associated with cortical microcircuit specialization and myelin (Burt et al, 2018;Ritchie, Pantazatos, & French, 2018). In contrast, recently a study with Parkinson disease patients showed a higher T1-w/T2-w ratio in the substantia nigra pars compacta compared to controls (Du, Lewis, Sica, Kong, & Huang, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Future ratio mapping studies with the same isotropic spatial resolution of the T1W and T2W images is thus required. Third, although the cortical T1W/T2W ratio is a parsimonious marker for neurodegenerative disease, however, it is still clear that how accurately it represents myelin contents (Righart et al, 2017; Yasuno et al, 2017; Du et al, 2019). Thus, it is possible that some pathological changes (iron deposition, free water or fiber density), other than demyelination, may also change T1W/T2W ratio.…”
Section: Discussionmentioning
confidence: 99%
“…Also, some recent work proposed the enhanced sensitivity of detecting changes in intracortical signal intensity associated well with the disease, such as multiple sclerosis, Parkinson disease, and normal subject with amyloid accumulation (Granberg et al, 2017; Righart et al, 2017; Yasuno et al, 2017). Thus, given that the T1W/T2W ratio is a clinically easy-to-implement measure, researchers regarded the technique as a parsimonious intracortical myelin marker (Du et al, 2019; Li et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In a study by Minati et al [ 39 ], the SN area of the PD patients was significantly smaller compared to that of HC subjects while no difference was found in a study by Oikawa et al [ 40 ]. Recently the SN pars compacta T1w/T2w ratio value on 3T MRI was proposed as a novel, parsimonious in vivo biomarker for the PD [ 41 ].…”
Section: Discussionmentioning
confidence: 99%